Recycling Strategies for Spent Consumer Lithium-Ion Batteries - Moritz Petzold; Sabine Flamme (Metals, 2024)
Introduction: In the quest for sustainable energy solutions and environmental protection, the management of end-of-life (EoL) batteries has emerged as a critical issue. Batteries, especially lithium-ion batteries (LIBs), power a wide range of devices and are central to modern life. As society’s reliance on batteries grows, there is an urgent need for sustainable battery recycling methods that can efficiently recover valuable materials, minimize environmental impact, and support the circular economy. Methods: A literature review was conducted to analyze the LIB market, the estimated return volumes and state-of-the-art sorting and recycling processes. Furthermore, a manual dismantling and input analysis was done for consumer LIB. Results: The current recycling processes operate for individual cathode active material input only. However, there is no sorting process or application in place to provide pre-sorted LIBs. This is why they need to be developed. X-ray transmission, X-ray fluorescence and optical sorting in theory can be applied to differentiate LIBs by their cathode active material. To support this hypothesis, further investigations need to be performed.